La morphologie externe et interne de la région supra-orbitaire est-elle corrélée à des contraintes biomécaniques ? Analyses structurales des populations d’Homo sapiens d’Afalou Bou Rhummel (Algérie) et de Taforalt (Maroc) - Antoine Balzeau; Jackie Badawi-Fayad (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The purpose of this study was to analyse and compare the external morphology of the supraorbital and maxillary regions as well as the variability of frontal pneumatisation in a sample of anatomically modern humans of the upper Palaeolithic of Afalou Bou Rhummel (Algeria) and Taforalt (Morocco), who underwent extraction of upper incisors. The results of the study show that the consequences of such mutilations are limited to the premaxilla and have no effect on the maxilla or the cranial superstructures. The supraorbital regions are homogeneous. However, the frontal pneumatisation, which is variable in its extension, has a similar morphology to the bone structures. Biomechanical stress has very limited influence on the development of the supraorbital structures, at least in modern humans.